Prevalence and genotypic characterization of antibiotic-resistant salmonella isolated from dogs, cats and snakes in Klang Valley, Malaysia - Abathcha, Mustapha Goni (2014)
Salmonellosis is a major zoonotic disease with worldwide occurrence and distribution. Salmonella species are ubiquitous in nature found in environment, humans and in intestines of wide range of animals. Most Salmonella infections in humans result from the ingestion of contaminated animal derived foods and contact with carrier animals. In veterinary medicine, antibiotics are used in livestock production, disease prevention and as supplement in feed additives. Multidrug resistant (MDR) in Salmonella is a cause of great concern in both clinical and veterinary medicine, because it limits the therapeutic options available for their treatment. The overall goals of the study were to determine the prevalence and antibiotic susceptibility of Salmonella in dogs, cats and snakes and to investigate the presence of resistant genes and class 1 integrons by Polymerase Chain Reaction (PCR). In addition,the Salmonella isolates were also characterised using Pulsed Field Gel Electrophoresis (PFGE) to determine genetic diversity. A total of 330 samples collected from 162 dogs, 126 cats and 42 snakes were examined for presence of Salmonella. The types of samples collected were rectal swabs from diarrheal and non-diarrheal dogs and cats at the University Veterinary Hospital at Universiti Putra Malaysia, Society for the Prevention of Cruelty to Animals (SPCA),Selangor and Dewan Bandaraya, Kuala Lumpur (DBKL), and cloacal swabs from captive and wild snakes from the Wildlife Department and Zoo Negara. Thirty-two nonrepeat isolates of Salmonella enterica were identified via conventional culture,biochemical, serological and PCR methods. Of the 32 (9.7%) Salmonella isolated from the samples, the prevalence of Salmonella shedding is 9.2% (15/162) of dogs, 0.8% (1/126) of cats and 38% (16/42) of the snakes. All the Salmonella isolates were found to carry invA gene after PCR amplification. Salmonella serovars identified were S. Typhimurium (n=5), S. Corvallis (n=10), S. Mbandaka (n=5), S. Agona (n=1), S. Poona (n=1) and S. Ruiru (n=1), and the remaining (n=9) of the isolates were untypable using the available antisera and regarded as Salmonella enterica. The Salmonella strains were evaluated for usceptibilities towards 12 commonly used antimicrobial from seven classes including aminoglycosides, beta-lactam, phenicols, sulfonamides, cephalosporin, flouroquinolone and tetracyclines. Fifty percent of the Salmonella strains were found to be resistant to the antimicrobial tested and 28% were multidrug resistant (MDR). Resistance to the following antibiotics was common among the isolates: tetracycline (40.6%), sulphamethazole-trimethoprim (18.7%), ampicillin (18.7%), chloramphenicol (15.6%), streptomycin (6.25%), enrofloxacin (12.5%),cephalexin (6.25%), cephalothin (6.25%) and amoxicillin-clavulanic acid (3.12%) was commonly seen in the Salmonella isolates. Based on the resistance phenotypes, antibiotic resistant Salmonella strains were selected for further characterisation for their antimicrobial resistance genes. Among 10 different resistance genes investigated in 16 antibiotic resistant isolates, seven genes were detected (blaTEM-1, strA, strB, sulII, dfrhI, tetA, and cmlA). The DNA sequence analysis of the resistance genes amplicons showed 90-100% homology with the respective genes in GenBank. Eleven of the tested Salmonella strains had class 1 integrons ranging from 0.2 to 1.5 kb. The results showed that resistance genes of streptomycin (strA, strB), ampicillin (blaTEM1), sulfonamides (Sul2), chloramphenicol (cm/A), trimethoprim (dhfrl) and tetracycline (tetA) were carried on chromosomal DNA. Molecular typing of the strains exhibited different plasmid profiles and PFGE patterns. Thirty Salmonella isolates were typable by PFGE generating 21 distinct pulsed-field profiles. The pulsotypes consisted of 12 to 19 XbaI-restricted fragments with sizes ranging from 22.5kb to 1135 kb. A wide diversity was found among the strains as evidenced by F-values, which ranged from 0.46 to 0.96. The dendrogram at >80% genetic similarity generated 9 clusters. This study confirmed that dogs might act as reservoir for antimicrobial resistance Salmonella. With this information, there is need for public campaign by the authority on the importance of zoonotic Salmonella to stakeholders in Malaysia.